The Effect of Giving Carrot Juice to Reduce Dysmenorrhea in S1 Nutrition Class 2022 Students at MH Thamrin University Jakarta Year 2024 - Monica Bella Putri Utami; Sulistiani Sulistiani (Oshada, 2025)
During menstruation, there are usually several disorders that occur, one of which is Dysmenorrhea. Dysmenorrhea is a condition of pain in the lower abdomen that usually occurs before and after menstruation that occurs continuously. This occurs because of contractions in women during menstruation. For its classification itself, it is divided into 2, namely primary and secondary. Usually this condition causes women who are about to or have finished menstruating to experience discomfort or pain in the lower abdomen and sometimes spread to the waist and even to the thighs, in addition to the disorders experienced also such as stomach cramps and headaches. There are many ways to reduce dysmenorrhea, one of which is by consuming carrot juice. Unbeknownst to many people, it turns out that carrots have many benefits not only for eye health but also to reduce pain during menstruation. This is due to the content of active compounds that are effective in reducing menstrual pain such as magnesium, calcium, and vitamins E and Betacarotene.